Functioning before and after a major depressive episode: pre-existing vulnerability or scar? A prospective three-wave population-based study. Issue 13 (14th January 2018) - Bos, E. H.; ten Have, M.; van Dorsselaer, S.; Jeronimus, B. F.; de Graaf, R.; de Jonge, P.
Abstract: Background: The vulnerability hypothesis suggests that impairments after remission of depressive episodes reflect a pre-existing vulnerability, while the scar hypothesis proposes that depression leaves residual impairments that confer risk of subsequent episodes. We prospectively examined vulnerability and scar effects in mental and physical functioning in a representative Dutch population sample. Methods: Three waves were used from the Netherlands Mental Health Survey and Incidence Study-2, a population-based study with a 6-years follow-up. Mental and physical functioning were assessed with the Medical Outcomes Study Short Form (SF-36). Major depressive disorder (MDD) was assessed with the Composite International Diagnostic Interview 3.0. Vulnerability effects were examined by comparing healthy controls ( n = 2826) with individuals who developed a first-onset depressive episode during first follow-up but did not have a lifetime diagnosis of MDD at baseline ( n = 181). Scarring effects were examined by comparing pre- and post-morbid functioning in individuals who developed a depressive episode after baseline that was remitted at the third wave ( n = 108). Results: Both mental ( B = −5.4, s.e. = 0.9, p < 0.001) and physical functioning ( B = −8.2, s.e. = 1.1, p < 0.001) at baseline were lower in individuals who developed a first depressive episode after baseline compared with healthy controls. This effect was most pronounced in people who developed a severe episode. No firm evidence of scarring in mental or physical functioning was found. In unadjusted analyses, physical functioning was still lowered post-morbidly ( B = −5.1, s.e. = 2.1, p = 0.014), but this effect disappeared in adjusted analyses. Conclusions: Functional impairments after remission of depression seem to reflect a pre-existing vulnerability rather than a scar.